Ultrasound-guided treatment of meralgia paresthetica: case report - Karamoy, Elvi Aprillia; Seputra, Desak Made Cittarasmi Saraswati; Sumada, I. Ketut; Desie Yuliani (International Journal of Advances in Medicine, 2023)
Meralgia paresthetica (MP) or so-called as lateral femoral cutaneous nerve (LFCN) entrapment is a mononeuropathy characterized by a localized area of paresthesia, dysesthesia, tingling, burning, and numbness on the anterolateral aspect of the thigh, between the inguinal ligament and the knee without associated loss of reflexes and motor weakness. The incidence of MP increases with obesity and diabetes. Ultrasound-guided has been demonstrated useful for visualization of peripheral nerves, in particular very small nerves such as the LFCN. Hereby, we reported a case of 63-year-old man diagnosed with MP. The patient complained of numbness, and no pain when pinched in his anterolateral aspect of the left thigh since 3 weeks ago. On physical examination, his body mass index (BMI) was 27 (overweight) with normal vital signs. Neurological examination revealed normal motoric function and refleks; but decreased sensation to pinprick in the left anterolateral thigh in the LFCN distribution. No abnormal findings on plain radiographs of the pelvis and lumbar spine. Ultrasound-guided injection was performed in this patient.